Close Communications: Hedge Funds, Brokers and the Emergence of Herding. (9th March 2016) - Kellard, Neil; Millo, Yuval; Simon, Jan; Engel, Ofer
Abstract : We examine how communication, evaluation and decision‐making practices among competing market actors contribute to the establishment of herding and whether this has impact on market‐wide phenomena such as prices and risk. Data are collected from interviews and observations with hedge fund industry participants in Europe, the USA and Asia. We examine both contemporaneous and biographical data, finding that decision‐making relies on an elaborate two‐tiered structure of connections among hedge fund managers and between them and brokers. This structure is underpinned by idea sharing and development between competing hedge funds leading to 'expertise‐based' herding and an increased probability of over‐embeddedness. We subsequently present a case study demonstrating the role that communication between competing hedge funds plays in the creation of herding and show that such trades affect prices by introducing an additional risk: the disregarding of information from sources outside the trusted connections.